PENGGUNAAN BERBAGAI TEKANAN DAN WAKTU HIDROLISIS PADA PRODUKSI GLUKOSAMIN HIDROKLORIDA DARI KITOSAN CANGKANG BEKICOT (Achatina fulica) - Noviana Linawati Dewi; Syaiful Bahri; Jaya Hardi (KOVALEN: Jurnal Riset Kimia, 2016)
ABSTRACT This study aims to determine the effect of pressure and time hydrolysis to produce glucosamine hydrochloride with the highest yield and the best quality of the chitosan of a snail shell. The study used a completely randomized design (CRD) factorial design consisting of 2 factors with 5 variations of hydrolysis time (40; 50; 60; 70 and 80) minutes and 2 variations of pressure (1 atm and 2 atm). Each treatment is done twice so obtained 20 experimental units. The highest glucosamine hydrochloride was obtained in hydrolysis time of 80 minutes and a pressure of 1 atm. Yield of 7,54%. Test of solubility in distilled water at 20°C was obtained of 3,79. Mol/L, while the maximum absorption of the UV-Vis with the addition of reagent Schales is at a wavelength of 420 nm. Keywords: Snails, Chitosan, Glucosamine, Hydrolysis Time, Pressure